Towards a balanced assessment of the viability of nuclear energy in the Philippines - Yap Josef T. (2021)
Nuclear energy in the Philippines has been thrust into the spotlight by the administration of President Duterte. A committee created by Executive Order 116 was tasked to formulate a national position a possible nuclear program. For nuclear energy to be a sustainable alternative, it must be accepted by society at large. Conventional wisdom surrounding the Bataan Nuclear Power Plant (BNPP) has branded this project as a white elephant leading to rejection of nuclear energy among a significant number of Filipinos, particularly members of civil society.
Keywords: Bataan Nuclear Power Plant; Nuclear power plants